2013
DOI: 10.1590/s0080-62342013000100024
|View full text |Cite
|
Sign up to set email alerts
|

Confirmação de presença de usuário à cirurgia eletiva por telefone como estratégia para reduzir absenteísmo

Abstract: RESUMOO presente trabalho trata-se de pesquisa quase experimental para avaliar o impacto na redução do absenteísmo de usuários agendados para cirurgia eletiva, quando submetidos à confirmação de presença por telefone. O estudo foi conduzido no Centro Cirúrgico do Hospital das Clínicas da Faculdade de Medicina de Botucatu, durante trinta dias, perfazendo 89 usuários. Os resultados indicaram a efetividade da intervenção, que reduziu o absenteísmo em 30%. Recomenda--se sua implementação na antevéspera da cirurgia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
0
2
0
12
Order By: Relevance
“…The same research also verified that the simple act of conforming the user's presence in the previous day, by telephone, was able to reduce these rates in up to 30%. 20 Partially similar to these data, another research conducted in a teaching hospital in São Paulo identified the main justifications for the cancellation as: unawareness of the date (18,33%), airway infection (15%) and other conditions (13,33%). 3 Yet another research conducted in an out-ofhospital surgical unit in the city of Rio de Janeiro identified the patient absenteeism (35%) and hypertensive crises (18%) as the main causes for surgical cancellations.…”
Section: Discussionmentioning
confidence: 72%
“…The same research also verified that the simple act of conforming the user's presence in the previous day, by telephone, was able to reduce these rates in up to 30%. 20 Partially similar to these data, another research conducted in a teaching hospital in São Paulo identified the main justifications for the cancellation as: unawareness of the date (18,33%), airway infection (15%) and other conditions (13,33%). 3 Yet another research conducted in an out-ofhospital surgical unit in the city of Rio de Janeiro identified the patient absenteeism (35%) and hypertensive crises (18%) as the main causes for surgical cancellations.…”
Section: Discussionmentioning
confidence: 72%
“…A prática de telefonar antes do dia da consulta para confirmar ou lembrar o usuário, o uso de mensagens de texto por telefone, carta ou e-mail, tiveram efeito positivo sobre o problema 17,32,33 .…”
Section: Algumas Possibilidades De Enfrentamento Ao Absenteísmounclassified
“…and more intense work with the medical team, who underestimate the surgical time and end up compromising other surgeries (Perroca, Jericó, & Facundin, 2007;Oliveira & Mendonça, 2014;Risso & Braga, 2010;Avila & Bocchi, 2013;Paschoal & Gatto, 2006). Inadequate clinical conditions and non-attendance are the most frequent causes of suspension of surgeries related to patients (Paschoal & Gatto, 2006;Perroca et al, 2007;Avila & Bocchi, 2013;González-Arévalo, Gómez-Arnau, DelaCruz, Marzal, Ramírez, et al, 2009;Kumar & Gandhi, 2012;Avila, Gonçalves, Martins & Moyses, 2012). The medical team appears with the main cause of suspension unrelated to the patient (Nascimento, Tillvitz, & Fonseca, 2013).…”
Section: Introductionmentioning
confidence: 99%